Real‐life effectiveness of biological therapies on symptoms in severe asthma with comorbid CRSwNP. Issue 5 (30th July 2021) - Mümmler, Carlo; Dünzelmann, Kristin; Kneidinger, Nikolaus; Barnikel, Michaela; Munker, Dieter; Gröger, Moritz; Canis, Martin; Behr, Jürgen; Koch, Andrea; Haubner, Frank; Milger, Katrin
Abstract: Background: We aimed to evaluate the effectiveness of different antibody therapies on nasal polyp symptoms in patients treated for severe asthma. Methods: We performed a retrospective analysis of patients with severe asthma and comorbid CRSwNP who were treated with anti‐IgE, anti‐IL‐5/R or anti‐IL‐4R. CRSwNP symptom burden was evaluated before and after 6 months of therapy. Results: Fifty patients were included hereof treated with anti‐IgE: 9, anti‐IL‐5/R: 26 and anti‐IL‐4R: 15 patients. At baseline median SNOT‐20 was similar among groups (anti‐IgE: 55, anti‐IL‐5/R: 52 and anti‐IL‐4R: 56, p = 0.76), median visual analogue scale (VAS) for nasal symptoms was 4, 7 and 8 ( p = 0.14) and VAS for total symptoms was higher in the anti‐IL‐4R group (4, 5 and 8, p = 0.002). After 6 months SNOT‐20 improved significantly in all patient groups with median improvement of anti‐IgE: −8 ( p < 0.01), anti‐IL‐5/R: −13 ( p < 0.001) and anti‐IL‐4R: −18 ( p < 0.001), with larger improvement in the anti‐IL‐4R group than in anti‐IgE ( p < 0.001) and anti‐IL‐5/R ( p < 0.001) groups. VAS nasal symptoms improved by median anti‐IgE: 0 (n.s.), anti‐IL‐5/R: −1 ( p < 0.01) and anti‐IL‐4R: −3 ( p < 0.001), VAS total symptoms by anti‐IgE: −1 (n.s.), anti‐IL‐5/R: −2 ( p < 0.001) and anti‐IL‐4R: −2 ( p < 0.001). Conclusions: Treatment by all antibodies showed effectiveness in reducing symptoms of CRSwNP in patients with severe asthma, with the largest reduction observed in anti‐IL‐4R‐treated patients.